THE IMPORTANCE OF PROFESSIONAL ETHICS FOR ACCOUNTANTS IN THE DIGITAL AGE - Azira Osmanović; Damir Šarić (Agora International Journal of Economical Sciences)
The digital age brings many challenges to the modern business world. Due to these significant challenges, the issue of ethics is gaining increasing attention. Ethics focuses on making moral decisions and acting upon them. Both in private and professional life, it is important to be honest, fair, and a good person. Ethics and ethical behavior are extremely important in the work of accountants, and they should apply the code of professional ethics for accountants. Proper application of professional ethics, rules, norms, laws, principles, and ethical codes significantly contributes to a positive work environment. The fundamental beliefs and value systems that accountants apply affect their work and, consequently, influence the trust in the results of their work. Financial statements provide information about an organization’s operations, and accountants are responsible for ensuring that this information is accurate and reliable. Nowadays, trust in financial statements has been significantly damaged, but when ethical norms are visibly applied in the behavior of accountants, it greatly influences the trust in their work and the accuracy of the data presented in financial reports. The subject of this research is to determine how significant the application of professional ethics of accountants is in the digital age. The goal is to identify how applying the International Code of Ethics for Professional Accountants contributes to the quality of accountants’ work. The paper presents the most important results of empirical research related to accountants’ perceptions of the importance of applying ethical principles in the accounting profession. The results show a high level of awareness among accountants regarding the importance of applying the highest ethical standards, which is encouraging and instills confidence in strengthening the integrity of the accounting profession in the future.